2020
DOI: 10.3390/diagnostics10090692
|View full text |Cite
|
Sign up to set email alerts
|

Association between EGFR Gene Mutation and Antioxidant Gene Polymorphism of Non-Small-Cell Lung Cancer

Abstract: EGFR mutation status is considered as an important predictor of therapeutic responsiveness in non-small-cell lung carcinoma patients. Recent evidence suggests that antioxidant gene polymorphisms are potential predictors of lung cancer risk. Thus, stratification of EGFR mutation-related phenotypes by antioxidant gene polymorphism status can be an effective approach in terms of improving the prognosis of lung cancer patients. The present study was designed to evaluate the distribution frequency of antioxidant ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…More than 1.3 million people are diagnosed with breast cancer each year, and about half a million die from the disease (16). Although several studies have been performed on the EGFR family gene in healthy and cancerous breast tissues, the association between some of its polymorphisms and the prognosis of the disease remains unclear (17,18). In the current study, we have developed a tetra ARMS PCR method for the detection and genotyping of ERBB4 rs13393577 T>C polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…More than 1.3 million people are diagnosed with breast cancer each year, and about half a million die from the disease (16). Although several studies have been performed on the EGFR family gene in healthy and cancerous breast tissues, the association between some of its polymorphisms and the prognosis of the disease remains unclear (17,18). In the current study, we have developed a tetra ARMS PCR method for the detection and genotyping of ERBB4 rs13393577 T>C polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants, such as the flavonoids found in haramonting, and antioxidant enzymes like SOD, CAT, GPX, and TRX, can restore blood levels that have been thrown off by the increased burden of ROS caused by DMBA ( Gusti et al,2021 ) as the cancer prevention and treatment relating to antioxidant systems. An intriguing study in this area found that Rhodomyrtus tomentosa produces glutathione, suggesting that blocking the glutathione and TRX signaling pathways can cause cancer cells to self-destruct and reduce their expression of the EGFR ( Lin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Curing individuals with LUAD remains difficult despite the positive clinical outcomes of molecularly targeted treatments. Thus, further research is required for the development of lung cancer treatments, particularly to identify relevant potential genetic markers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%